Emerging Compounds Removal from Wastewater Natural and Solar Based Treatments - Lofrano, Giusy; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2012)
In the last years the release of emerging pollutants such as Endocrine Disruptors (EDCs), Pharmaceuticals and Personal Care Products (PPCPs) into the environment has raised great concern. While investigating how to treat emerging pollutants from water and wastewater, researchers have drawn attention on the implementation of more environmentally friendly technologies able to achieve high removal efficiency at low costs.  Emerging Compounds Removal from Wastewater by Green Technologies: Natural and Solar Based Treatments introduces green chemistry in relation to these treatment technologies. More specifically, this volume: • Reviews the suitability of alternative adsorption processes that use natural adsorbents natural materials or agricultural waste in light of the inefficiency of conventional wastewater treatment plants; • Evaluates the potential of constructed wetlands for the removal of some categories of trace contaminant of worldwide relevance in view of their application as decentralized systems; • Highlights the promising role of a special class of oxidation techniques defined as Advanced Oxidation Processes (AOPs) supported by sunlight. This volume will be of great interest to students, technicians, and academics alike who are interested in evaluating  and selecting the technologies that lead to better and more sustainable treatment of this huge class of pollutants.
Keywords: Chemical engineering; Water-supply.; Environmental chemistry; Water pollution; Industrial Chemistry/Chemical Engineering; Water Industry/Water Technologies; Environmental Chemistry; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution